脉冲频率控制电路、控制系统及其控制方法 (2024)
一种脉冲频率控制电路、控制系统及控制方法。脉冲频率控制电路包含第一和第二比较电路、档位切换电路、斜率判定电路、触发器电路。第一比较电路用以根据电源转换电路的输出电压输出第一信号。档位切换电路用以根据电源转换电路的输出电流输出档位切换信号。斜率判定电路用以输出斜率调制电压，并根据档位切换信号决定斜率调制电压具有第一或第二斜率。第二比较电路用以根据斜率调制电压输出第二信号。触发器电路用以根据第一和第二信号输出控制信号至电源转换电路。当斜率调制电压具有第一或第二斜率时，控制信号相应具有第一或第二频率。第一频率高于第二频率。 The invention discloses a pulse frequency control circuit, a control system and a control method. The pulse frequency control circuit comprises a first comparison circuit, a second comparison circuit, a gear switching circuit, a slope judgment circuit and a trigger circuit. The first comparison circuit is used for outputting a first signal according to the output voltage of the power conversion circuit. The gear switching circuit is used for outputting a gear switching signal according to the output current of the power conversion circuit. The slope judgment circuit is used for outputting a slope modulation voltage and determining whether the slope modulation voltage has a first slope or a second slope according to the gear switching signal. The second